Explaining ontogenetic shifts in root–shoot scaling with transient dynamics - Lohier, Théophile (Oxford University Press, 2014)
BACKGROUND AND AIMS: Simple models of herbaceous plant growth based on optimal partitioning theory predict, at steady state, an isometric relationship between shoot and root biomass during plant ontogeny, i.e. a constant root–shoot ratio. This prediction has received mixed empirical support, suggesting either that optimal partitioning is too coarse an assumption to model plant biomass allocation, or that additional processes need to be modelled to account for empirical findings within the optimal partitioning framework. In this study, simulations are used to compare quantitatively two potential explanations for observed non-isometric relationships, namely nutrient limitation during the experiments and initial developmental constraints. METHODS: A simple plant growth model was built to simulate the growth of herbaceous species, based on optimal partitioning theory combined with empirically measured plant functional traits. Its ability to reproduce plant relative growth rate and final root weight ratio was assessed against previously published data. Predicted root–shoot ratios during plant ontogeny were compared with experimental observations. The effects of nutrient limitation and initial developmental constraints on root–shoot ratios were then tested. KEY RESULTS: The model was found to reproduce overall plant growth patterns accurately, but failed, in its simplest form, at explaining non-isometric growth trajectories. Both nutrient limitation and ontogenetic developmental constraints were further shown to cause transient dynamics resulting in a deviation from isometry. Nitrogen limitation alone was not sufficient to explain the observed trajectories of most plant species. The inclusion of initial developmental constraints (fixed non-optimal initial root–shoot ratios) enabled the reproduction of the observed trajectories and were consistent with observed initial root–shoot ratios. CONCLUSIONS: This study highlights the fact that considering transient dynamics enables theoretical predictions based on optimal partitioning to be reconciled with empirically measured ontogenetic root–shoot allometries. The transient dynamics cannot be solely explained by nutrient limitation during the experiments, pointing to a likely role for initial developmental constraints in the observed non-isometric growth trajectories.